Multiplexed cancer biomarker detection using chip-integrated silicon photonic sensor arrays. Issue 18 (12th July 2016) - Washburn, Adam L.; Shia, Winnie W.; Lenkeit, Kimberly A.; Lee, So-Hyun; Bailey, Ryan C.
Abstract : A multiplexed cancer biomarker panel developed on a silicon photonic sensor array platform is promising for organ-specific disease stratification. Abstract : The analysis of disease-specific biomarker panels holds promise for the early detection of a range of diseases, including cancer. Blood-based biomarkers, in particular, are attractive targets for minimally-invasive disease diagnosis. Specifically, a panel of organ-specific biomarkers could find utility as a general disease surveillance tool enabling earlier detection or prognostic monitoring. Using arrays of chip-integrated silicon photonic sensors, we describe the simultaneous detection of eight cancer biomarkers in serum in a relatively rapid (1 hour) and fully automated antibody-based sandwich assay. Biomarkers were chosen for their applicability to a range of organ-specific cancers, including disease of the pancreas, liver, ovary, breast, lung, colorectum, and prostate. Importantly, we demonstrate that selected patient samples reveal biomarker "fingerprints" that may be useful for a personalized cancer diagnosis. More generally, we show that the silicon photonic technology is capable of measuring multiplexed panels of protein biomarkers that may have broad utility in clinical diagnostics.